Agricultural science policy: changing global agendas - Alston, Julian M.; Pardey, Philip G.; Taylor, Michael J. (International Food Policy Research Institute, 2001)
Technological advances developed through R&D have supplied the world with not only more food, but better food. This report looks at issues raised by this changing environment for agricultural productivity, agricultural R&D, and natural resource management.